PENERAPAN MODEL PROJECT BASED LEARNING DALAM PEMBELAJARAN MATERI CAHAYA DAN ALAT OPTIK UNTUK MEMICU KETERAMPILAN BERPIKIR KREATIF SISWA SMP - Saiya, Yulinco; Harahap, Fransiska; Poluakan, Cosmas (LPPM Politeknik Saint Paul Sorong, 2024)
Creative thinking skills are important as one of the skills needs of the 21st century. The aim of this research is to determine the level of students’ creative thinking abilities using the Project Based Learning model in learning the topic of Light and Optical Devices. Type of pre-experimental research with One-Shot Case Study. The research subjects were Junior High School students with purposive sampling (n=25). Data collection used the Creative Thinking Instrument test. Data analysis is quantitative descriptive. Ideas are collected and then fluency, flexibility, and originality scores are calculated based on the Creative Thinking Skills Rubric. The research results show that both classically and individually, students’ creative thinking abilities according to the fluency and flexibility indicators are less creative, and according to the originality indicators they are quite creative. The research conclusion is that the level of students’ creative thinking using the Project Based Learning model on the topic of Light and Optical Devices is in the less creative category. The Project Based Learning model can trigger students’ creative thinking abilities.